America's corner store : - Bacon, John U. (Wiley, 2004)
America’s Corner Store details the incredible story of this innovative company, from its inception as a family-run store in 1901 to its transformation as one of the largest food and drug retailers in the world. Readers will learn how superb management, modern merchandising, innovative store design, fair pricing, outstanding customer service, and an exceedingly high-quality pharmacy fueled Walgreens astounding growth and continued success. From their invention of the malted milkshake to their creation of drive-thru pharmacies, Walgreens has set the standard for the industry. Through firsthand accounts of company executives and extensive research, John Bacon has created the most accurate and up-to-date account of this storied franchise.